THE USE OF LEARNING RESOURCES FOR HIGH SCHOOL GEOGRAPHY TEACHERS AT MGMP DKI JAKARTA - Muin, Abdul; Panjaitan, Antonius; Hotimah, Oot; Zid, Muhammad (Jurnal Pendidikan Ilmu Sosial, 2024)
Geography education is an integral part of the education curriculum in Indonesia, especially at the senior secondary education level. This research is intended to find out how high school geography teachers who are members of the Subject Teachers' Conference (MGMP) in DKI Jakarta utilize various learning resources. The research method used was a survey using questionnaires to geography teachers. The respondents in this study were 15 people who were geography teachers from various high schools who were active in the DKI Jakarta MGMP. Data was collected through a questionnaire which included questions about the type of learning resources used, frequency of use, effectiveness according to teacher perceptions, and obstacles faced in using these learning resources. The analytical method applied in this study is the use of descriptive statistics. Based on research results, it shows that the majority of geography teachers use a variety of learning resources in teaching, including textbooks, digital materials, online sources, and other sources. This research provides valuable insights for improving curriculum and teacher training in the area of using learning resources in geography learning in high school. Thus, the use of learning resources by high school Geography teachers at MGMP DKI Jakarta highlights the importance of diversification, quality and accessibility of learning resources in improving the quality of Geography learning. Collaboration between the government, educational institutions and educational groups is needed to facilitate the use of diverse and quality learning resources for Geography teachers in DKI Jakarta.